The Macaque Cerebellar Flocculus Outputs a Forward Model of Eye Movement - Kim, Gyutae; Laurens, Jean; Yakusheva, Tatyana A.; Blazquez, Pablo M. (Frontiers in Integrative Neuroscience, 2019)
The central nervous system (CNS) achieves fine motor control by generating predictions of the consequences of the motor command, often called forward models of the movement. These predictions are used centrally to detect not-self generated sensations, to modify ongoing movements, and to induce motor learning. However, finding a neuronal correlate of forward models has proven difficult. In the oculomotor system, we can identify neuronal correlates of forward models vs. neuronal correlates of motor commands by examining neuronal responses during smooth pursuit at eccentric eye positions. During pursuit, torsional eye movement information is not present in the motor command, but it is generated by the mechanic of the orbit. Importantly, the directionality and approximate magnitude of torsional eye movement follows the half angle rule. We use this rule to investigate the role of the cerebellar flocculus complex (FL, flocculus and ventral paraflocculus) in the generation of forward models of the eye. We found that mossy fibers (input elements to the FL) did not change their response to pursuit with eccentricity. Thus, they do not carry torsional eye movement information. However, vertical Purkinje cells (output elements of the FL) showed preference for counter-clockwise eye velocity (corresponding to extorsion [outward rotation] of the ipsilateral eye). We hypothesize that FL computes an estimate of torsional eye movement since torsion is present in Purkinje cells but not in mossy fibers. Overall, our results add to those of other laboratories in supporting the existence in the CNS of a predictive signal constructed from motor command information.